Maternal near miss events: a retrospective observational study in a tertiary care centre of central India - Dadhich, Ruchita; Guin, Gita; Rawat, Sarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Clinically women who have survived complications during pregnancy and childbirth termed as Maternal Near Miss. The major reasons and causes are the same for both Maternal Near Miss and Maternal Death, so review of MNM cases is likely to yield valuable information regarding severe morbidity, which could lead to death of the mother, if not intervened properly and in time. Investigating the instances of severe morbidity may be less threatening to providers because the woman survived. Methods: It was a retrospective study conducted at the Department of Obstetrics & Gynaecology NSCB Medical College Jabalpur, Madhya Pradesh, India. Data of maternal death and maternal near miss was collected from the previous records from 1st January 2017 to December 2017 according to WHO 2009 criteria. Results: Total number of near miss cases was 164 and total number of Maternal Death was 111. Maternal Near Miss incidence ratio was 28.70 per 1000 live births. Maternal Near Miss to Maternal Mortality Ratio was 1.46 and Mortality index was 40.36%. Common cause of Near Miss events was hypertensive disorders of pregnancy - 85 cases (51.82%), followed by hemorrhage - 39 cases (23.78%). heart disease- 9 cases (5.48%) was also common during pregnancy. Conclusions: In summary, this study shows that besides 111 cases who died, there were another 164 cases who survived due to the prompt diagnosis and treatment received in our set- up However, the overall high incidence of near-miss to maternal mortality (1.46) indicates that a significant proportion of critically ill patient still die of these complications. Maternal near miss reviews will be the best tool for the betterment of community and health care systems.